Kebijakan, Implementasi dan Isu Strategis Pendidikan Bagi Individu Berkebutuhan Khusus - Aini Mahabbati (Jurnal Pendidikan Islam, 2014)
Special education is designed to provide educational services for individuals with special needs in order to achieve the appropriate potency and capacity. The implementation of special education starts with understanding the learners. Therefore, the identification and assessment of student learning needs must be from the first basic step, followed by adjustment of curriculum and learning. The nature of the curriculum is individual contextual-and functional, with a range of education from early childhood until the age of transition to further education or future adult life. Special education strategic issues developed in a line of developments in the equal rights of all people access education, and they moved from the segregation paradigm to an inclusive paradigm. The special education that is growing discourse is also influenced by social dynamics, economics, politics, culture, and religion.